KETERLIBATAN SISWA SEKOLAH DASAR DALAM EKSTRAKURIKULER DAN PENGARUHNYA TERHADAP KETERAMPILAN SOSIAL - Zafirah Nur Amalia; Sabrina Putri Salsabila; Naila Kamila Anandhita; Decenni amelia (STKIP Subang, 2025)
Student involvement in extracurricular activities plays a very important role in developing social skills. This study aims to analyze student involvement in extracurricular activities and their influence on social skills. Extracurricular activities not only provide opportunities for students to explore their interests and talents, but also involvement in extracurricular activities can help students develop social skills, such as communication, cooperation, empathy, and problem-solving skills. The method used in this study is a literature review, where a literature review is a study used to collect information and data with the help of various materials available in the library such as documents, books, journals, articles and others. by reviewing various previous studies related to the relationship between involvement in extracurricular activities and students' social skills. Based on the literature analysis, it was found that students who actively participate in extracurricular activities, such as sports, scouts, or arts, tend to have better social skills. Thus, to obtain optimal results, it is necessary to select extracurricular activities that are in accordance with the social needs of students, as well as efforts to create a supportive environment for them to develop.